Reminiscences of Brian G. Gardiner (1932–2021): Reminiscences of Brian G. Gardiner (1932–2021) - Viloria, Ángel L. (Anartia, 2021)
Professor Brian G. Gardiner (born October 30th, 1932), a British paleontologist and zoologist, passed away at the age of 88 on January 21st, 2021. We received this sad news with deep regret. Linked for more than sixty-five years to various academic institutions in London, Brian became an influential scientist, recognized and appreciated world-wide, both for his original contributions to the study of fossil fish and for his personal charisma. He will be remembered as a first class supervisor of students of various nationalities. In this last aspect he left a Gardinerian School scattered over the five continents. His scientific career was very early related to the paleontological collections of The Natural History Museum (NHMUK). There he cultivated best friends among colleagues and participated in controversial discussion circles made up mostly of paleontologists, ichthyologists, entomologists, and botanists. He was even reputed to have been a founding member of a little but noisy “gang of four” ichthyologists (Reid et al. 2021). Over the years, an extraordinary international network of academic relationships and friends was built around Brian Gardiner.